Efficient and Stereoselective Nitration of Olefins with AgNO2 and TEMPO - Maity, Soham; Naveen, Togati; Sharma, Upendra; Maiti, Debabrata (Synlett, 2014)
Synthetic utility of nitroolefins in fundamental organic synthesis has inspired us to develop a method to access nitroolefins stereoselectively starting from olefins. Silver nitrite along with catalytic TEMPO was found to be the reagent combination of choice. The method enjoys a broad scope and functional-group tolerance while nitroolefins are obtained in high yields with excellent E-selectivity.
Keywords: nitroolefin; stereoselective; olefin; nitration; high yields